Baseline MRI bone erosion predicts the subsequent radiographic progression in early rheumatoid arthritis patients who achieved sustained good clinical response. Issue 6 (2nd November 2017) - Tamai, Mami; Arima, Kazuhiko; Nakashima, Yoshikazu; Kita, Junko; Umeda, Masataka; Fukui, Shoichi; Nishino, Ayako; Suzuki, Takahisa; Horai, Yoshiro; Okada, Akitomo; Koga, Tomohiro; Kawashiri, Shin-ya; et al.
Abstract: Objective: To examine whether magnetic resonance imaging (MRI) findings at baseline predict radiographic progression in early-stage rheumatoid arthritis (RA) patients who have achieved sustained good clinical response. Methods: This is a sub-analysis from the one-year observational study of Nagasaki University Early Arthritis Cohort. Definition of 'good clinical response' was a decrement of disease activity score (DAS) 28 ≧ 1.2 at three months with achievement of DAS28 remission through 6–12 months. Gd-enhanced MRI of both wrists and finger joints were examined at baseline and scored using rheumatoid arthritis magnetic resonance imaging score (RAMRIS). Annual increment of Genant-modified Sharp score (GSS) > 0 was defined as 'radiographic progression'. Predictors of radiographic progression were determined by logistic regression analysis. Results: Twenty-four subjects were selected in the present study. Each median RAMRIS synovitis, bone edema, bone erosion, and GSS at baseline were 6.5, 0.5, 0, and 0, respectively. Five patients developed radiographic progression at one year. Multivariate logistic regression analysis has shown that RAMRIS bone erosion at baseline is the only independent predictor of radiographic progression at one year ( p  = .032). Conclusions: Our data suggest that MRI bone erosion predicts poor radiographic outcome of early-stage RA even if it has been successfully treated.